Indigenous Movements and Their Impact on The Linguistic Rights of Ethnic Groups in Colombia - Hipia Chamorro, Jenyffer (Millcayac - Revista Digital de Ciencias Sociales, 2025)
The struggles of indigenous movements in Colombia have achieved recognition and legislation on native languages in the national territory. Initially, through regional and local processes in which the recognition and appreciation of native languages led to the issuance of mandates that gradually transcended their incorporation into Colombian law. This required a series of social conditions that promoted the formation of indigenous organizations and, with this, their influence on national legislation, from their participation in the 1991 constitution, which recognizes the country as multi-ethnic and multicultural, to the creation of the 2010 language law, which stipulates the official status of indigenous languages in their territories and the inclusion of their teaching in schools and universities.